MASALAH ONTOLOGI DALAM KAJIAN KEISLAMAN - Jabbar Sabil (Universitas Islam Negeri Ar-Raniry, 2014)
Some muslim scholars offer the project of Islamization of Knowledge in order to undertake the development of Islamic studies. However, this offer was rejected by some others on the grounds that it is closely related problem of the ontological foundation of science, which is the basic assumption of the material object. As a result of Islamization science project is considered insignificant by Islamic parties offering Islamization of science. This problem might have been solved by answering the problems on the ontology in Islamic studies in order to obtain a moderate perspective. This paper discuses it by using the philosophical approach of critical rationalism (metaphysical realism), and use deductive method to do falsification test. This study found that ontology is the reality of Islamic studies in the form of text: 1) the physical reality of the text of the Quran; 2) the metaphysical reality of the Quranic texts. The value of both texts reality applied into the pure science so it is integrated with Islamic studies. Then the findings of pure intellect sciences are accepted as a source of knowledge to understand the text, so that the study of Islamic sciences will be connected to pure science.